2013
DOI: 10.1186/1472-684x-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care research on the island of Ireland over the last decade: a systematic review and thematic analysis of peer reviewed publications

Abstract: BackgroundAs palliative care research continues to expand across Europe, and the world, questions exist about the nature and type of research undertaken in addition to the research priorities for the future. This systematic review, which is the first stage of a larger scale study to identify the research priorities for palliative care on the island of Ireland, examined palliative care research conducted on the island over the last decade.MethodsA comprehensive search strategy was implemented and strict eligibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 22 publications
4
34
2
Order By: Relevance
“…Studies conducted in the scope of community, in populations suffering from non-oncological diseases and pediatric populations were scarce. In these areas of palliative care there are clear gaps in knowledge production, which could be explored in future research and are consistent with results of similar international studies (6,28) . The most investigated target populations were students/health professionals (38.51%), followed by patients (25.86%).…”
Section: Discussionsupporting
confidence: 79%
“…Studies conducted in the scope of community, in populations suffering from non-oncological diseases and pediatric populations were scarce. In these areas of palliative care there are clear gaps in knowledge production, which could be explored in future research and are consistent with results of similar international studies (6,28) . The most investigated target populations were students/health professionals (38.51%), followed by patients (25.86%).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, to further develop PC research, critical analysis in terms of characteristics of national PC research is desirable. A limited number of national evaluations of research conducted in the field have been reported, and these show the field to be dominated by observational study designs and by a lack of measurement of outcomes, sampling limitations and strong emphasis on need‐based investigations . Further, in cases where national reviews of research have been reported, these are considered a baseline for future analysis of trends.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the initiation of a treatment on the basis on what is believed to be effective is no longer considered good clinical practice [4]. A clinician in addition to his clinical expertise, must have access to the best available evidence, should carefully appraise its quality and assess its applicability to each individual patient [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Whilst this may be beneficial, questions exist around the type and quality of the research being undertaken. Previous reviews have concluded that PC studies were largely descriptive, with a wide variation in sample size, in demographic and clinical aspects and with a lack of use of recognised standard measures and consideration of key outcomes [5, 6, 9–12]. Visser et al [5] studied the reality of evidence-based practice in palliative care and highlighted additional problems like unpowered studies, recruitment difficulties and high attrition rates, inadequate duration of follow-up and difficulty in defining outcomes and avoiding performance bias [5, 9, 13].…”
Section: Introductionmentioning
confidence: 99%